2019
DOI: 10.3390/cells8121639
|View full text |Cite
|
Sign up to set email alerts
|

Knock Down of Plakophillin 2 Dysregulates Adhesion Pathway through Upregulation of miR200b and Alters the Mechanical Properties in Cardiac Cells

Abstract: Background: Mutations in genes encoding intercalated disk/desmosome proteins, such as plakophilin 2 (PKP2), cause arrhythmogenic cardiomyopathy (ACM). Desmosomes are responsible for myocyte–myocyte attachment and maintaining mechanical integrity of the myocardium. Methods: We knocked down Pkp2 in HL-1 mouse atrial cardiomyocytes (HL-1Pkp2-shRNA) and characterized their biomechanical properties. Gene expression was analyzed by RNA-Sequencing, microarray, and qPCR. Immunofluorescence was used to detect changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The graphs show that the median value of the Young's modulus measured in HL-1 PKP2 cells was higher than that measured in HL-1 R735X cells ( Figure 1B). Puzzi et al using AFM in HL-1 cells showed that PKP2 knock-down was also associated with decreased cellular stiffness, as indicated by decreased Young's modulus, when comparing to control groups (Puzzi et al, 2019).These results support the observation that R735X cells lack most stress and F-actin fibers ( Figure 1C). Images from the top central area of cells revealed a scarcity of F-actin filaments in the area above the nucleus of cells expressing the R735X mutant (46.05%±0.73% in PKP2 cells vs. 26.05%±1.48% in R735X cells; p<0.0001, ****; n=11) ( Figure 1C).…”
Section: Mutant R735x Expression Alters Actin Cytoskeleton and Cellulsupporting
confidence: 78%
See 1 more Smart Citation
“…The graphs show that the median value of the Young's modulus measured in HL-1 PKP2 cells was higher than that measured in HL-1 R735X cells ( Figure 1B). Puzzi et al using AFM in HL-1 cells showed that PKP2 knock-down was also associated with decreased cellular stiffness, as indicated by decreased Young's modulus, when comparing to control groups (Puzzi et al, 2019).These results support the observation that R735X cells lack most stress and F-actin fibers ( Figure 1C). Images from the top central area of cells revealed a scarcity of F-actin filaments in the area above the nucleus of cells expressing the R735X mutant (46.05%±0.73% in PKP2 cells vs. 26.05%±1.48% in R735X cells; p<0.0001, ****; n=11) ( Figure 1C).…”
Section: Mutant R735x Expression Alters Actin Cytoskeleton and Cellulsupporting
confidence: 78%
“…It is known that PKP2 loss impairs cortical actin remodeling and normal desmosome assembly (Godsel et al, 2010), which compromises cell mechanical properties like cellular stiffness (Puzzi et al, 2019). We measured cell stiffness in intact HL-1 cardiac cells by acquiring force-volume maps by atomic force microscopy (AFM).…”
Section: Mutant R735x Expression Alters Actin Cytoskeleton and Cellulmentioning
confidence: 99%
“…The molecular basis of ECM organization and remodeling in ACM is still under-investigated. Recently few papers identified a signature of ACM cardiac cell microRNAs, known to be involved in ECM turnover and mechanosensing (Rainer et al, 2018;Puzzi et al, 2019).…”
Section: Cardiac Extracellular Matrix Regulationmentioning
confidence: 99%
“…Results of in vitro and in vivo studies indicate that abnormalities in biomechanical properties of the desmosome, as well as of the cross-talk between the desmosomes and other cellular structures such as the cytoskeleton, nucleus, gap junctions, and ion channels, contribute to the pathogenesis of ACM [ 1 , 17 , 18 , 19 , 41 , 81 , 82 , 83 , 84 ].…”
Section: Molecular Pathogenic Pathwaysmentioning
confidence: 99%